Gaya Kepemimpinan Kepala Ruang Dengan Kepuasan Kerja Perawat - Muhammad Rijali Rahman; Endang Pertiwiwati; Ichsan Rizany (JURNAL KEPERAWATAN RAFLESIA, 2020)
Nurse job satisfaction is one of the factors affecting work productivity. Job satisfaction is influenced by the leadership style applied by the chief nurse in leading his subordinates. The purpose of this study was determined the relationship between the leadership style of the chief nurse and the nurse's job satisfaction in the inpatient room at Idaman City Hospital in Banjarbaru. This research approach used cross sectional. The population was all nurses in the inpatient room with a total of 119 nurses. Sampling used quota sampling as many as 102 respondents. There were 3 research instruments used, consisted of questionnaire respondent characteristics, nurse job satisfaction and leadership style of the chief nurse. The method used by events that carry out actions on respondents, has been observed. The correlational and survey approaches used in this study were to present a questionnaire. The leadership style of nurse manager has an average of 57.90 (50-72). Nurse job satisfaction has rather average of 62,82 (38-96). There was a relationship between the leadership style of the chief nurse and the nurse's job satisfaction in the inpatient room at Idaman City Hospital in Banjarbaru (p-value = 0,000 <0.05). The leadership style of the head of the room in accordance with the situation and conditions and good application can produce nurses who are satisfied with their work and can also improve performance in carrying out their duties.